Kritik Terhadap Pandangan Orientalis William Muir dalam Memahami Sirah Nabawiyah - Emil Nasrulloh; Daud Rashid; Nunun Zainun (UIN Sunan Gunung Djati Bandung, 2023)
This study is a critical evaluation of William Muir's biography, Life of Mohammad – From Original Sources (1923). Muir (d. 1905) was an Oriental scholar and evangelical Christian from Scotland who was known in India as a British civil servant and experience dealing with Indian people, especially Muslims, prompted him to write a biography of Muhammad. He was one of the first modern scholars to categorize primary source material from classic biographies and transform them into modern biographies of Muhammad's life. In doing so, he combined post-Enlightenment methodology with his Christian sensibilities and aimed his work as an evangelical missionary at work on compiling his biography. Muir's biographical work contributed significantly to a genre of European literature which used exclusively authentic Muslim sources. This study will critically evaluate how Muir uses the Koran as the main source of his biography.